2018
DOI: 10.1017/s0007114518002477
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term low-dose folic acid supplementation on degree of total homocysteine-lowering: major effect modifiers

Abstract: We sought to examine the potential modifiers in the association between long-term low-dose folic acid supplementation and the reduction of serum total homocysteine (tHcy) among hypertensive patients, using data from the China Stroke Primary Prevention Trial (CSPPT). This analysis included 16 867 participants who had complete data on tHcy measurements at both the baseline and exit visit. After a median treatment period of 4·5 years, folic acid treatment significantly reduced the tHcy levels by 1·6 μmol/l (95 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The extent by which such criteria have been adopted in published trials will be considered in our comments below. Critically, the interpretation of the results must take into account that the effect of B vitamins may be very different in different populations or subgroups of the population, as most convincingly demonstrated in the China Stroke Primary Prevention Trial (CSPPT, to be described below) [54].…”
Section: Homocysteine and Disease Prevention – Clinical Trials Of B Vitamin Supplementationmentioning
confidence: 99%
“…The extent by which such criteria have been adopted in published trials will be considered in our comments below. Critically, the interpretation of the results must take into account that the effect of B vitamins may be very different in different populations or subgroups of the population, as most convincingly demonstrated in the China Stroke Primary Prevention Trial (CSPPT, to be described below) [54].…”
Section: Homocysteine and Disease Prevention – Clinical Trials Of B Vitamin Supplementationmentioning
confidence: 99%
“…Participants with higher neutrophil counts had lower folate and elevated tHcy levels at baseline. Folic acid is effective in lowering tHcy levels (31,32) . Elevated tHcy has been reported to be an independent determinant of the development of albuminuria (33) .…”
Section: Laboratory Resultsmentioning
confidence: 99%
“…Our research revealed that history, hypertension, stroke, CHD, and Hcy were statistically meaningful between the success group and the failure group. Wang et al [10] found that the efficacy of oral folic acid therapy may be influenced by sex, baseline Hcy level, and smoking. A study explored the influence factors of the old's Hcy level in Beijing, and they concluded that Hcy level may be associated with education, blood folate levels, age, sex, and drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Oral folic acid therapy is the most common intervention in HHcy therapy to reduce the concentration of Hcy [10]. However, at home and abroad, the conclusions of the previous studies on the efficacy of folic acid therapy to HHcy were inconsistent [11][12][13].…”
Section: Introductionmentioning
confidence: 99%